(untitled) (Proceedings of the International Conference on Education, 2021)
Academic Institutions utilize various ICT mechanisms to manage institution data, retrieve information, sustain financial activities, and deal with digital culture to create the learning and teaching setting. Thus, Enterprise Architecture (EA) is the ICT strategy employed in the domain to engage with radical changes and permuting trends. The purpose of EA is to organize and standardize Information Technology (IT) components to align with institution’s goals. Qualitative analysis was conducted to discover the factors that instigated the first academic institution in the Philippines to adopt EA as an ICT tool for its long-term strategy. The approach was an exploratory research design to closely examine data through thematic analysis, focusing on inductive reasoning that emphasizes the data convened from the semi-structured interviews with an open-ended question. The result of the interviews was graded as primary and secondary factors which influenced the adoption process. Primary factors are the elements that drives the EA adoption such as the organizational structure and human traits, while secondary factors consist of the characteristics of the transformation, specifically the intended techniques, proposed transformation capabilities, transformation obstacles and institutional perspectives. The purpose of this enquiry is to disseminate the primary and secondary factors, discovered from the first academic institution in the Philippines, to various academic institutions and other sectors with similar settings, as a learning ground and bedrock of future possibilities for EA adoption. Thus, the challenge for subsequent EA adopters is to utilize and strengthen the primary and secondary factors to boost the success of transformation for competitive advantage. The future research should gravitate towards factors of EA non-adoption in academic institutions and other sectors as EA is still emerging slowly particularly in the Philippines.